2019
DOI: 10.1001/jamanetworkopen.2019.14611
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chorioamnionitis With Bronchopulmonary Dysplasia Among Preterm Infants

Abstract: Key PointsQuestionIs chorioamnionitis a risk factor for developing bronchopulmonary dysplasia in preterm infants?FindingsThis systematic review, meta-analysis, and metaregression found that chorioamnionitis was associated with an increased risk of bronchopulmonary dysplasia in preterm infants but also found significant differences in baseline characteristics between infants with and infants without chorioamnionitis. A multivariate metaregression model combining the difference in gestational age and the odds of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
123
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 217 publications
(591 reference statements)
9
123
3
1
Order By: Relevance
“…18 The hypothesis that inflammation exposure accelerated functional lung maturation but increased the vulnerability of the preterm lung to postnatal injury is still unresolved and CA has been associated with increased, decreased, or no risk of either BPD or RDS. [33][34][35] A recent systematic review showed that CA was associated with an increased risk of BPD in preterm infants. This association may be modulated by GA and by the risk of respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…18 The hypothesis that inflammation exposure accelerated functional lung maturation but increased the vulnerability of the preterm lung to postnatal injury is still unresolved and CA has been associated with increased, decreased, or no risk of either BPD or RDS. [33][34][35] A recent systematic review showed that CA was associated with an increased risk of BPD in preterm infants. This association may be modulated by GA and by the risk of respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…14 Although the relationship between CA and BPD has not been consistent across different studies, a recent meta-analysis supports the possible role of CA in the pathogenesis of BPD. 15 Analyzing 158 studies that met inclusion criteria, this meta-analysis showed that CA exposure was significantly associated with BPD at 28 days (65 studies; odds ratio [OR]: 2.32; 95% confidence interval [CI]: 1.88-2.86; p < 0.001; heterogeneity: I 2 ¼ 84%; p < 0.001) and BPD at 36 weeks (108 studies; OR: 1.29; 95% CI: 1.17-1.42; p < 0.001; heterogeneity: I 2 ¼ 63%; p < 0.001). The association between CA and BPD remained significant for both, clinical and histologic CA.…”
mentioning
confidence: 99%
“…28 These findings are consistent with clinical observations of increased lung inflammation after chorioamnionitis and the increased risk of BPD when the infants are mechanically ventilated. 3 The plasma levels for budesonide were slightly lower than previously reported, but this may have been due to the initial volume resuscitation needs or LPS-induced leaky lungs. 21 The amount of budesonide remaining in the lungs, either as free budesonide or converted to a budesonide ester, was low (<2% on initial results) in the animals consistent with previous reports.…”
Section: Discussionmentioning
confidence: 55%
“… 1 , 2 Chorioamnionitis increases the risk of development of bronchopulmonary dysplasia (BPD), and mechanical ventilation may further increase BPD risk. 3 , 4 Chorioamnionitis can be experimentally modeled through intra-amniotic (IA) injection of Escherichia coli lipopolysaccharide (LPS) in preterm sheep. 5 , 6 Forty-eight hours after IA LPS, lung inflammation, interstitial edema, and a modest decrease in lung compliance occurs in preterm lambs.…”
Section: Introductionmentioning
confidence: 99%